Upaya Guru Pendidikan Agama Islam Dalam menumbuhkan Minat Baca Dan Tulis Al-Quran Di Madrasah Aliyah Negeri 2 Surakarta - Rein Sampoerno, Yockie, Dr.Syamsul Hidayat M.Ag, Drs. Zaenal Abidin MPd (2016)
ABSTRACT Interest for reading and writing of Qur'an among some Moslem adolescent Indonesia at this time began to decrease. That way also was happened in environment of MAN 2 Surakarta. The lack of learning interest to reading and writing of Qur'an couldcause by several factors. In the end, the task of Islamic Education teacher was the one to attempt to increase reading and writing Qur'an interest on these students. Various attempts were made by the teacher for the sake of it success or failure of these efforts rely heavily on the various factors that influence it. Based on the background of the above problems could be formulated issues to be studied were: "How the efforts of Islamic Religious Teacher was increase the reading and writing interest of Qur'an at the students in MAN 2 Surakarta 2015/2016academic year. Type of this research was classified as field research. The data collecting methodwas used documentation, observation and interviews. Meanwhile, to analyze the results of this study, was used qualitative descriptive approach consisted of five activity that wascollecting data and analyze entire data from various source(interviews, observation, and documentation), reducing data, then filter matching with theory and formula of the problem, data presented in narrative form, and conclusion withdrawal. This research result were forms of encouragement given the Islamic Education teacher to the students as early as possible was to provide an understanding of mastering reading and writing of Qur'an importance. Advantage obtained by students was to the condition of in this time having many colleges giving expense gratos to hafizh Qur'an. Its expectation with this motivation hence student earn more motivated and impelled to learn by heart of Qur'an. Keywords:Efforts Teacher, Islamic Education, Interest reading and writing Qur'an interest, MAN (State High Islamic School) 2.